Inhalation effect of massoilactone from massoia essential oil on lipid profile, liver tissues, and body weight of Sprague Dawley rat - Irmanida Batubara & , Yanico Hadi Prayogo, Irma Herawati Suparto & , Berry Juliandi, Susumu Uchiyama (Journal of Applied Pharmaceutical Science, 2019)
Massoia (Cryptocarya massoia) is an Indonesian endemic plant containing essential oils with massoia lactone as a dominant compound component. This study aims to clarify the inhalation effect of massoia lactone on body weight and lipid profile on Sprague Dawley rats. Chemical components of two fractionated portions among four fractions from massoia oil were identified to be composed of 97% and 1.4% massoia lactone, thus named as massoia lactone rich and poor fractions, respectively. The two fractions and massoia oil were further used for in vivo tests on four treatment groups (one group was negative control). The results showed that the experimental animals that inhaled massoia lactone rich fraction had the lowest body weight analysis of variance (ANOVA p < 0.05), while the animals that inhaled massoia oil and poor massoia lactone fraction had the lowest average cholesterol and triglyceride concentrations (ANOVA p < 0.05). These data indicate that the inhalation of fractionated massoia oil has the potential to decrease body weight, restrain inclining of triglycerides and cholesterol concentration in the blood. Also, the number of liver cells with a larger size than normal liver cells in rats with massoia lactone rich and poor fraction treatment was less than the negative control and treated with massoia oil.
Keywords: Massoilactone, massoia oil, body weight, lipid profile, liver tissues.